Using data on offender mobility in ecological research - Hesseling, Rene B. P. (Journal of quantitative criminology, 1992)
This article presents some findings on neighborhood structure, police recorded crime, and offender mobility for the city of Utrecht, the Netherlands. The highest crime rates were found in the inner-city neighborhoods. The findings further show that the occurrence of different types of petty crime in residential neighborhoods is associated with different neighborhood characteristics. It was found that offenders reside predominantly in lower-social status neighborhoods. Using data on offender mobility it is shown that violent crime and vandalism are the more locally committed crimes, as compared to residential burglary and other property crime. Finally, it is proposed that data on offender mobility can be used to gain more insight into the link between certain neighborhood characteristics and crime.